ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TAX AVOIDANCE (Studi Kasus pada Perusahaan Pertambangan dan Pertanian yang Terdaftar pada Bursa Efek Indonesia Periode 2012-2016) - Eva Noor Iskandar, 14.05.52.0185; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2018)
This study aimed to examines the influence of leverage, Audit Commitee, Institutional Ownership, Profitability, Firm Size, Fiscal Lost Compensation on the Tax Avoidance. This research was conducted at Indonesia by using analysis unit mining and agriculture company that have gone public. The population of this research are mining and agricultureÂ company that listed in Indonesia Stock Exchange. The sampling method using purposive sampling with the study period of 2012 until 2016 and obtained as many as 41 companies. The technique of data analysis is used multiple regression analysis. The results of this study shows that leverage, Profitability, Firm Size, Fiscal Lost Compensation does not affect on Tax Avoidance. Audit Commitee and Institutional Ownership significant positive influence on Tax Avoidance. The asset structure significant negative influence on Tax Avoidance.Keyword: Leverage, Audit Commitee, Institutional Ownership, Profitability, Firm Size, Fiscal Lost Compensation and Tax Avoidance